2015 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2015
DOI: 10.1109/icsm.2015.7332508
|View full text |Cite
|
Sign up to set email alerts
|

Choosing your weapons: On sentiment analysis tools for software engineering research

Abstract: Abstract-Recent years have seen an increasing attention to social aspects of software engineering, including studies of emotions and sentiments experienced and expressed by the software developers. Most of these studies reuse existing sentiment analysis tools such as SentiStrength and NLTK. However, these tools have been trained on product reviews and movie reviews and, therefore, their results might not be applicable in the software engineering domain.In this paper we study whether the sentiment analysis tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…This paper builds on our previous work (Jongeling et al 2015). The current submission extends it by reporting on replication of two recent studies (Section 5).…”
Section: Replications and Negative Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…This paper builds on our previous work (Jongeling et al 2015). The current submission extends it by reporting on replication of two recent studies (Section 5).…”
Section: Replications and Negative Resultsmentioning
confidence: 65%
“…This paper builds on our previous work (Jongeling et al 2015). The current submission extends it by reporting on a follow-up study (Section 3.3), replication of two recent studies (Section 5) as well presenting a more elaborate discussion of the related work below.…”
Section: Related Workmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, their performances may underachieve the expectations or in the worst case lead to wrong results. Limited to sentiment analysis, Jongeling et al [6] showed that general purpose tools such as SentiStrength and NLTK were unreliable for assessing sentiments in technical prose within issue comments.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that this is a fitting estimate of the sentiment in the review. As inferred by Jongeling et al in [12], the scores obtained from SentiStrength do not necessarily tally with those from other sentiment analysis APIs. We reassure the same empirically for drug review data, by drawing up a comparison of normalized sentiment scores Table II) for review sample sizes ≥ 30.…”
Section: Extraction and Feasibility Of Usingmentioning
confidence: 77%